Increased Levels of Activated Factor VII and Decreased Plasma Protein S Activity and Circulating Thrombomodulin during Use of Oral Contraceptives - Quehenberger, Peter; Loner, Uta; Kapiotis, Stylianos; Handler, Sylvia; Schneider, Barbara; Huber, Johannes; Speiser, Wolfgang (Thrombosis and Haemostasis, 1996)
In the present study the effect of oral contraceptive (OC) treatment on selected factors involved in the activation, i.e. circulating activated factor VII (cFVIIa), and in the inhibition of blood coagulation, i.e. plasma protein S activity and circulating thrombomodulin (cTM), were for the first time measured in OC users in a prospective study. Beside other coagulation variables, these parameters were measured during treatment with three low estrogen formulations containing different gestagen components (norgestimate, gestodene). During OC treatment increases in the activation markers prothrombin fragment F1+2 and D-Dimer were found, suggesting an increased activation of blood coagulation and fibrinolysis. Along with elevated plasma levels of FVII antigen, cFVIIa was also found increased in all three treatment groups, while inhibitory components of blood coagulation, plasma protein S activity and cTM, significantly and similarily decreased during treatment in all three treatment groups. We conclude that low dose estrogen pills induce similar changes in the plasma levels of main regulatory components of blood coagulation, despite differences in their gestagen components. Increased levels of activators and decreased activities of inhibitors may contribute to arterial and venous thrombotic complications seen in predisposed OC users.